Communication network robust routing optimization in an integrated energy cyber–physical system based on a random denial-of-service attack - Fan, Hong; Huang, Xu; Wang, Diwei; Zhou, Boyang (Frontiers in Energy Research, 2024)
The integration of power grids and communication networks in smart grids enhances the safety and reliability of the power system. However, this interdependence also makes the entire network vulnerable to network attacks on the communication network, leading to chain failures. Denialof-Service (DoS) attacks, specifically targeting the consumption of route bandwidth, pose a significant threat to the quality-of-service of real-time automation control data transport. In this study, we propose an evaluation index for service information flow and communication links to optimize the routing mode, considering the failures caused by such attacks. Furthermore, a single service evaluation index is insufficient to effectively assess the importance of communication links in the integrated energy cyber-physical system (IECPS). To address this, we incorporate both security and economic service evaluation indexes to quantify the significance of information flow routing. Subsequently, the IECPS including electric, heat, and gas routing optimization model in worst scenario is proposed, which is solved by using a column and constraint generation algorithm. The results demonstrate that the resulting routing method enables the circumvention of the specified attack area, significantly reducing the correlation degree of communication links within the attack area compared to before optimization. Moreover, comparison with single-service optimization methods demonstrates the superiority of this method.